Case Series of Staphylococcus aureus Bacteremia With Discordant Genotypic and Phenotypic Categorization of Methicillin Susceptibility. Issue 6 (November 2020) - Gulliver, Jessica; Jung-Hynes, Brittney; Chen, Derrick J.
Abstract : Background: Methicillin-susceptible/methicillin-resistant Staphylococcus aureus (MSSA/MRSA) can be directly identified from positive blood culture bottles using molecular methods, but discrepancies with phenotypic testing occasionally occur. We sought to determine the incidence and clinical impact of these discrepancies. Methods: Positive blood culture bottles are routinely tested in the hospital laboratory for mecA via the Xpert MRSA/SA blood culture assay which uses real-time polymerase chain reaction (PCR), and antimicrobial susceptibility testing (AST) via MicroScan PC33 is performed on recovered S. aureus isolates; discrepancies between the Xpert MRSA/SA blood culture assay and AST are resolved by repeat and supplemental testing. A retrospective review of medical and laboratory data from January 2015 to June 2018 was performed on all patients that had discordant Xpert MRSA/SA blood culture assay and AST results. Results: Approximately 1410 PCR assays were performed, and there were 6 (0.4%) cases with discordant AST results. Five cases were classified as MSSA by PCR but MRSA by AST, and 1 case was classified as MRSA by PCR but MSSA by AST. For the former group, antimicrobial therapy was changed in 3 patients to cover MRSA, whereas the remaining 2 patients were already being treated for MRSA; for the latter case, the patient was treated for MRSA during the initial hospitalization but was later readmitted with disseminated MSSA. Discrepancies were likely due to presence of an staphylococcal cassette chromosome mec variant (n = 2), borderline oxacillin resistance (n = 1), heterogeneous MRSA (n = 1), or undetermined (n = 2). Conclusions: Rapid identification of MRSA bacteremia via PCR provides actionable information to direct empiric treatment. The PCR results are highly accurate, though are infrequently not corroborated by AST due to various reasons.